Modified Tricycles as Public Transport during Tidal Flooding Events: The Case of Tikling in Hagonoy, Bulacan, Philippines - Liberty Aimee R. Umali; Imre C. Recto; Rchielein S. Lansangan; Landriel Dane G. Torres; Eleonor R. Basilio (Three E Science Institute, 2023)
Public transportation is one of the sectors most affected by high tides in Hagonoy, Bulacan, Philippines. To overcome the challenges posed by these tides, local tricycles, a form of public transportation, have been modified with elevated sidecars and driver's seats that remain above the water level. These modified tricycles are locally known as Tikling. This study aims to identify the perceived risks associated with public transportation, specifically Tikling, during tidal flooding events in selected Barangays in Hagonoy, Bulacan, Philippines. The researchers employed a mixed-method design to gather the necessary information and address the study's objectives. Data were collected from 161 respondents, including 130 passengers, 25 Tikling drivers, and six representatives from local government units and the Municipal Disaster Risk Reduction Management Office. The findings revealed that passengers perceive riding Tikling under different weather conditions, flood levels, and ground clearance to pose moderate risks, as indicated by a mean score of 6.42, and that floods contribute to increased travel time and fare. The recommendations from the local government units include revisiting tariffs to establish accurate travel fees, conducting an Education Information Campaign to raise awareness about the risks associated with traveling, improving the structural quality of Tikling, and promoting coordination between the Pedicab Tricycle Operators and Drivers Associations (PETODA), a local association of tricycle drivers, and the local government office. The study suggests standardizing Tikling to minimize the risks involved. This standardization should address factors such as ground clearance, materials used, and the appropriate design of these modified public vehicles.